(untitled) (Research, Society and Development, 2021)
This study refers to an analyze of patients of an tracheostomized intensive care unit for adults. It´s about a descriptive study with documental characteristic, containing a quantitave and transversal, approach through the analyze of patients medical record hospitalized during the period of January 2020 to august 2020 of both genders with the age between 16 and 89 years old, been approved by the committee of Ethics in Research with an opinion number of 4.898.929. Statistically analyzed through the Bioestat Software. 5.3 used p≤0,05 for the statistical significance. There were 51 medical records in which predominated the diagnosis of COVID-19 with 84,3%, howbeit 07,8% were surgical/oncological, 03,9% infectious, 02,0% surgical/cardiovascular and 02,0% cause by sickle cell anemia. Regarding the total time of mechanical ventilation (MV), when we compare the discharge and the deaths we had a significant result, it was observed in the deaths case that 76,5% were between 16 and 30 days in intensive care and 23,5% stayed more than 30 days. Regarding the time of the mechanical ventilation after making the tracheostomy there was no significant association between discharge and deaths.